Modulation of total electron content by global Pc5 waves at low latitudes. Issue 1 (1st January 2016) - Vorontsova, E.; Pilipenko, V.; Fedorov, E.; Sinha, A.K.; Vichare, G.
Abstract: Earlier studies have successfully demonstrated that the GPS–TEC technique is a powerful method to study the propagation pattern of transient disturbances in the ionosphere. This technique has turned out to be sensitive enough to detect ionospheric signatures of ULF waves as well, particularly at high latitudes. It has already been reported earlier that during the recovery phase of the strong magnetic storm on Oct. 31, 2003, intense Pc5 geomagnetic activity was accompanied with distinct pulsations of the same periodicity in the TEC data from high-latitude GPS receiving stations. The present study reveals the identical features in geomagnetic and TEC data at low-latitude stations in the Indian sector as well. However, the presented observational results on TEC modulation by global Pc5 waves at low latitudes cannot be interpreted on the basis of the Alfven mode concept. The most promising mechanism that can explain the present observations is the plasma compression by fast magnetosonic mode. Theoretical order-of-magnitude estimates of the ratio between pulsation amplitudes in TEC and geomagnetic field based on the proposed mechanism is found to be about the same as the observed values.